A case of gamasoidosis associated with exposure to a wild lorikeet feeding tray. (16th June 2015) - Warren, Matthew; Tritton, Sara; Abbott, Nicola CD; Sim, Sarah; Strutton, Geoffrey M; Soyer, H Peter
Abstract: Gamasoidosis (acariasis, avian‐mite dermatitis or bird‐mite dermatitis) is caused by members of the mite superfamily Dermanyssoidea. The mites lay their eggs on the nest of the birds they feed on. The also leave the nest and feed on humans if there is no bird host available. The bites result in urticated plaques and papules. Here we present a case of gamasoidosis from exposure to a wild lorikeet feeding tray.